Association of vitamin D3 and its metabolites in patients with and without type 2 diabetes and their relationship to diabetes complications. (September 2020) - Butler, Alexandra E.; Dargham, Soha R.; Latif, Aishah; Mokhtar, Haira R.; Robay, Amal; Chidiac, Omar M.; Jayyousi, Amin; Al Suwaidi, Jassim; Crystal, Ronald G.; Abi Khalil, Charbel; Atkin, Stephen L.
Background: Epidemiological studies have suggested that vitamin D deficiency is associated with the development of type 2 diabetes (T2DM) and is related to diabetes complications. This study was undertaken to determine the relationship between diabetes complications and cardiovascular risk factors with vitamin D3 and its metabolites: 1, 25-dihydroxyvitamin D3 (1, 25(OH)2 D3 ), 25-hydroxyvitamin D3 (25(OH)D3 ), 24, 25-dihydroxyvitamin D3 (24, 25(OH)2 D3 ); and 25-hydroxy-3epi-vitamin D3 (3epi25(OH)D3 ). Methods: 750 Qatari subjects, 460 (61.3%) with and 290 (38.7%) without T2DM, who were not taking vitamin D3 supplements, participated in this cross-sectional, observational study. Plasma concentrations of vitamin D3 and its metabolites were measured by liquid chromatography tandem mass spectrometry analysis. Results: T2DM subjects had lower concentrations of all vitamin D3 metabolites ( p  < 0.001) except 3epi25(OH)D3 ( p  < 0.071). Males had higher concentrations of all vitamin D3 metabolites ( p  < 0.001). In the T2DM subjects, lower 25(OH)D3 was associated with retinopathy ( p  < 0.03) and dyslipidemia ( p  < 0.04), but not neuropathy or vascular complications; lower 1, 25(OH)2 D3 was associated with hypertension ( p  < 0.009), dyslipidemia ( p  < 0.003) and retinopathy ( p  < 0.006), and coronary artery disease ( p  < 0.012), but not neuropathy; lower 24, 25(OH)2 D3 concentrations were associated with dyslipidemia alone ( p  < 0.019); 3epi25(OH)D3 associated with diabetic neuropathy alone ( p  < 0.029). In nondiabetics, 25(OH)D3, 1, 25(OH)2 D3 and 24, 25(OH)2 D3 were associated with dyslipidemia ( p  < 0.001, p  < 0.001, p  < 0.015, respectively) and lower 1, 25(OH)2 D3 was associated with hypertension ( p  < 0.001). Spearman's correlation showed 1, 25(OH)2 D3 to be negatively correlated to age and diabetes duration. Conclusions: Different diabetes complications were associated with differing vitamin D parameters, with diabetic retinopathy related to lower 25(OH)D3 and 1, 25(OH)2 D3 levels, hypertension significantly associated with lower 1, 25(OH)2 D3, while dyslipidemia was associated with lower 25(OH)D3, 1, 25(OH)2 D3 and 24, 25(OH)2 D3. While 25(OH)D metabolites were lower in females, there was not an exaggeration in complications.